Estudio de factibilidad para desarrollar la mancomunidad en el manejo de residuos sólidos de las parroquias de Dureno y Pacayacu, cantón Lago Agrio, provincia de Sucumbíos - Pérez, Rubén Homero (2014)
This research is about a feasibility study to develop the community due to an appropriate solid waste management in the town of Dureno and Pacayacu, Lago Agrio, Province of Sucumbíos. The same research has the order to establish a technical, economical and social opportunity of building a strong commonwealth in Dureno and Pacayacu with an efficient and appropriate disposal of solid wastes and facilitate legal instruments for people. This study starts from a research that point out the history, geographical location, education levels, employment, dwelling, access to basic services and present situation of the solid waste management in each town. Although, it has a complete research of different factors such as legal, technical, institutional, social and financial items of the level of service that the solid waste management needs. With the information of the towns and the institutional condition of the disposal of solid waste management, it concludes that the biggest weakness of the waste service is the final treatment that it has in each town. Both throw their wastes with any kind of treatment techniques to reduce impacts on the environment.